2023
DOI: 10.21203/rs.3.rs-2502537/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation aberrancy is a reliable prognostic tool in uveal melanoma

Abstract: Background: Despite outstanding advances in understanding the genetic background of uveal melanoma (UM) development and prognosis, the role of DNA methylation reprogramming remains elusive. This study aims to clarify the extent of DNA methylation deregulation in the context of gene expression changes and its utility as a reliable prognostic biomarker. Methods: Transcriptomic and DNA methylation landscapes in 25 high- and low-risk UMs were interrogated by Agilent SurePrint G3 Human Gene Expression 8×60K v2 Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(68 reference statements)
0
1
0
1
Order By: Relevance
“…A recent study using UM tissue from 68 UM patients in Slovakia revealed that high-risk tumors had a total of 7810 CpGs that were hypomethylated and 16,588 that were hypermethylated. Three genes with hypomethylation or upregulation, HTR2B (FC 191.4), AHNAK2 (FC 12.6), and CALHM2 (FC 7.8), as well as six genes with hypermethylation or downregulation, SLC25A38 (FC-4.6), EDNRB (FC-4.7), TLR1 (FC-8.6), RNF43 (FC-10.8), IL12RB2 (FC-18.1), and MEGF10 (FC-25) were selected for validation and the number of CpGs inversely correlated with gene expression [ 108 ].…”
Section: Uveal Melanoma and Dna Methylationmentioning
confidence: 99%
“…A recent study using UM tissue from 68 UM patients in Slovakia revealed that high-risk tumors had a total of 7810 CpGs that were hypomethylated and 16,588 that were hypermethylated. Three genes with hypomethylation or upregulation, HTR2B (FC 191.4), AHNAK2 (FC 12.6), and CALHM2 (FC 7.8), as well as six genes with hypermethylation or downregulation, SLC25A38 (FC-4.6), EDNRB (FC-4.7), TLR1 (FC-8.6), RNF43 (FC-10.8), IL12RB2 (FC-18.1), and MEGF10 (FC-25) were selected for validation and the number of CpGs inversely correlated with gene expression [ 108 ].…”
Section: Uveal Melanoma and Dna Methylationmentioning
confidence: 99%
“…Ao buscar genes apoptóticos regulados por RMEL3, encontramos que como gene altamente aumentado no silenciamento de RMEL3 o MEGF10, que codifica uma proteína transmembrana tipo I altamente expressa no sistema nervoso central, que em melanoma uveal demonstrou ter papel crucial na inibição da progressão tumoral além de aumentar a apoptose celular (Yang et al, 2021). A expressão de MEGF10 é reprimida epigeneticamente pela hipermetilação do DNA ou pela metilação H3K27/K9 em linhas celulares de neuroblastoma e de melanoma uveal (Charlet et al, 2017;Soltysova et al, 2023), e pode ser por esse mecanismo que RMEL3 reprime a expressão de MEGF10 em A375, visto que análises anteriores do nosso grupo demonstraram alta expressão de RMEL3 correlaciona com uma hipermetilação do genoma em melanoma (Goedert, 2019).…”
Section: Discussionunclassified